Wind loads of moving vehicle on bridge with solid wind barrier. (1st February 2018) - Xiang, Huoyue; Li, Yongle; Chen, Suren; Hou, Guangyang
Highlights: The wind loads of a moving vehicle model on a bridge installed with a solid wind barrier are tested by wind tunnel tests. The effects of different heights of wind barriers and wind directions on the wind loads acting on the vehicles are analyzed. The protective effects of wind barriers for the moving vehicle are discussed. Abstract: A wind tunnel experimental study is conducted to study the wind loads acting on a moving vehicle model on a bridge installed with a solid wind barrier. The repeatability of the tests is verified by the cases with different wind and vehicle speeds. For comparison purposes, the difference of the results between the static and moving vehicle models are discussed. The effects of different heights of wind barriers and wind directions on the wind loads acting on the vehicles are analyzed. Finally, the wind loads acting on the vehicles are further evaluated to assess the potential impact of wind barriers on traffic safety. The results show that the relative movement between the vehicle, bridge and solid wind barriers affects the aerodynamic characteristics of the vehicle. The variation patterns of aerodynamic characteristics with different yaw angles are altered by the solid wind barriers with different heights, and there is a most unfavorable yaw angle for the protective effect of solid wind barriers in terms of side force. The wind direction has some impact on the five-component coefficients of vehicles after installing a solid wind barrier. However, the solid wind barrier has similar protective efficiency in terms of the side force acting on the vehicle under different wind directions.